STOCK INVESTMENT ANALYSIS ON SAVINGS LEVEL AMONG MEDAN CITY STUDENTS - RS, Prawidya Hariani; Fahreza, Muhammad Rizky (Proceeding International Seminar of Islamic Studies, 2024)
There is instability in the development of LQ45 and KOMPAS100 shares in 2018 – 2022. There are factors that influence the sale of LQ45 index shares. Lack of student interest in investing in ordinary shares ( common stock ). The aim of this research is to carry out a descriptive economic analysis of the development of LQ45 and KOMPAS100 shares in 2018 - 2022. To estimate the factors that influence sales of LQ45 index shares. Analyze the determining factors of student interest in investing in common stocks in the KOMPAS100 index. The research method used is using multiple OLS via the E-Views 12 application and carrying out factor analysis using the Smart PLS application. The data used is a time series, namely monthly data from 2018-2022. The results of this research are that loan interest rates, inflation and GDP have a significant influence on LQ45 at α15%. And the results of factor analysis show that cultural factors do not have a significant influence on students' interest in investing in shares in the city of Medan.